2015
DOI: 10.5152/anatoljcardiol.2015.6214
|View full text |Cite
|
Sign up to set email alerts
|

GuideLiner catheter application in complex coronary lesions: experience of two centers

Abstract: Objective:GuideLiner catheter provides adequate back-up support and a coaxial guide engagement for stent delivery in complex coronary anatomies. In this study, we aimed to present one of the largest series of experience with GuideLiner catheter utilized for challenging percutaneous coronary interventions in two centers.Methods:We retrospectively collected the coronary angiography records of 64 patients between January 1, 2012 and August 1, 2014 in whom conventional techniques failed for stent delivery and 5-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
4
8
0
Order By: Relevance
“…The mean depth of intubation in our study was 42 ± 19 mm (minimum for ostial lesion of LCX, and maximum 92 mm for SVG graft) (Fig. 10c), which is similar to that reported by Chan et al [5] and Dursun et al [14] though the longest intubation depth is 120 mm as reported by Ma et al [15]. Much deeper intubation of Guidezilla device may cause entire segment to prolapse outside ostium of coronary artery, impairing withdrawal of device, and with loss of co-axiality.…”
Section: Discussionsupporting
confidence: 91%
“…The mean depth of intubation in our study was 42 ± 19 mm (minimum for ostial lesion of LCX, and maximum 92 mm for SVG graft) (Fig. 10c), which is similar to that reported by Chan et al [5] and Dursun et al [14] though the longest intubation depth is 120 mm as reported by Ma et al [15]. Much deeper intubation of Guidezilla device may cause entire segment to prolapse outside ostium of coronary artery, impairing withdrawal of device, and with loss of co-axiality.…”
Section: Discussionsupporting
confidence: 91%
“…In our present study, the lesion morphologyis very much similar to Dursun et al (2016) 12 who presented a 64 patients study using the GuideLiner ® catheter, with the majority of patients having ACC/AHA types B2/C lesions.In the present study success of stent deployment is 16 out of 19 cases (84.2%), which also very much resembles the study by to Dursun et al (2016) 12 , although it was through trans-femoral route. In addition, we found that this device showed an excellent safety profile since no coronary dissection was induced.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have shown the safety and utility of GuideLiner catheter in complex coronary interventions involving ACC/AHA type B2 or C lesions . GuideLiner is an important adjunctive tool in CTO interventions where it is difficult to deliver a balloon or microcatheter across the lesion .…”
Section: Discussionmentioning
confidence: 99%